The Experience and Needs of Teachers in Providing Reproductive Health Education in Adolescents with Intellectual Disability - Barkah Wulandari; Apri Nur Wulandari (Indonesian Journal of Global Health Research, 2021)
Adolescents with intellectual disabilities are teenagers who have a low level of intelligence compared to adolescents of their age. This situation causes adolescents with intellectual disabilities have an inability to adapt a developmental behavior. It happens because they have the same biological development as adolescents of their age, thus often causing various problems related to reproduction. On the other hand, teachers in schools have obstacles in providing reproductive health education, this is because many teachers have not received information on reproductive health, consider it taboo, especially on the topic of sexuality and the limitations of children's abilities. So, the teacher’s role is limited to reminding or helping young girls to change pads when menstruating, helping and reminding them how to clean themselves after urinate or defecate. The objective of this research is to explore the experience and needs of teachers in providing reproductive health education in adolescents with intellectual disabilities. This research was conducted using a qualitative approach. Participant in this research was teachers in SLB Negeri 2 Yogyakarta. The data were collected using Focus Group Discussion (FGD) method. There are 4 themes based on this study, namely: adolescents with intellectual disabilities are feeling the need for sexuality, school efforts in controlling sexual abuse of adolescents with intellectual disabilities in schools, efforts to increase teacher capabilities in providing reproductive health material, teacher limitation regarding the reproductive health of adolescents with intellectual disabilities. Reproductive health curriculum, teaching instruments, parental participation for the sustainability of reproductive health materials at home, and material reproductive health curriculum in each age stage are the need of teachers in providing reproductive health for adolescent with intellectual disabilities.